Formulation approaches to improving the delivery of an antiviral drug with activity against seasonal flu. (8th November 2013) - Sammeta, Srinivasa M.; Wang, Li; Mutyam, Shravan K.; O'Loughlin, Kathleen; Green, Carol E.; Werner, Milton H.; Kelly, Terence; Shankar, Gita N.
Abstract: The main objective of the present study was to develop formulations of noscapine hydrochloride hydrate with enhanced solubility and bioavailability using co-solvent- and cyclodextrin-based approaches. Different combinations of co-solvents, which were selected on the basis of high-throughput solubility screening, were subjected to in vitro intestinal drug permeability studies conducted with Ussing chambers. Vitamin E tocopherol polyethylene glycol succinate and propylene glycol based co-solvent formulations provided the maximum permeability coefficient for the drug. Inclusion complexes of the drug were prepared using hydroxypropyl-β-cyclodextrin and sulphobutylether cyclodextrins. Pharmacokinetic studies were carried out in male Sprague–Dawley rats for the selected formulations. The relative bioavailabilities of the drug with the co-solvent- and cyclodextrin-based formulations were found to be similar.